Portal Dosimetry as a patient specific Quality Assurance tool for Volumetric Arc Radiotherapy - Rathore, Vikram; Mr. V.K Mishra; Dr. V Choudhary; Mr. G.S. Gautam; Ms. P. Kushawaha; Dr. S.K. Azad; Dr. M. Kerketta; Dr P.K. Chandrakar; Dr R.S. Singh; Dr. R.R. Jain (International Journal of Medical Research and Review, 2021)
Introduction: Volumetric Arc Radiotherapy (VMAT) is an advanced technique. Calculations of VMAT plans are not so accurate even with State-of-Art dose calculation algorithms due to their complexity. Hence pre-treatment patient specific Quality Assurance (QA) of each VMAT plan is required. In the present study Electronic Portal Imaging Device (EPID) based portal dosimetry system was used for pre-treatment patient specific QA. Material and Methods: A total of 50 patients were chosen in this study. Verification plans of each patient were calculated for portal dosimetry then executed on the EPID system to measure the spatial distribution of radiation dose. Calculated and measured dose distribution were compared to evaluate Gamma Index (GI) passing criteria of Dose Difference (DD) of 3% and Distance–to-Agreement (DTA) of 3mm, Area Gamma (γ≤) >95%, Average Gamma (Ave) <0.5% and Maximum Gamma (Max) <3.5%. Results: The mean values of Area Gamma (γ% ≤1) were observed to be varied from 99.14±0.23% to 99.87±0.18%. The Mean Values of Average Gamma (Ave) are found to vary from 0.19±0.05% to 0.15±0.04% and the mean values of Maximum Gamma (Max) found to be varied from 1.94±0.37% to 1.59±0.41%. All the plans were passed the gamma index criteria with very good agreement. Thus the use of Portal Dosimetry for pre-treatment patient QA is found to be a very useful, quick, precise, efficient and effective pre-treatment patient specific QA tool for VMAT treatment. Conclusion: Portal Dosimetry can be utilized for routine use for patient specific quality assurance for Volumetric Arc Radiotherapy treatment.